Sport psychological skills that distinguish successful from less successful soccer teams - Coetzee, B.; Grobbelaar, H. W.; Gird, C. C. (Journal of Human Movement Studies, 2006)
In spite of the fact that soccer has arnong the highest participants of all sports in the world, there is a lack of research that pertains to the possible influence that sport psychological skills may have on the performances of soccer players. It is in the light of this problem that this study was undertaken to determine which sport psychological skills distinguish successful from less successful soccer teams. Thirty-six soccer players of two tertiary institutions completed four sport psychological questionnaires (CSAI-2, AMSSE, ACSI-28 and PSI), by means of which a total of 21 sport psychological skills were measured. The results of the effect size analysis revealed that the successful group obtained significantly higher scores (d=Q.&) for the striving for success psychological skill (32.8±4.14) compared to the less successful group (29.6rt4.29). The successful group also reached significantly higher (d=Q.5) concentration, coachability and mental rehearsal values than the less successful group, who recorded significantly better values (d=Q.5) in their freedom from worry score. A forward, stepwise discriminant analysis showed that the following skills were the most important discriminators between successful and less successful soccer teams: mental rehearsal (PSI), concentration (ACSI-28 and PSI), peaking under pressure (ACSI-28), goal setting/ mental preparation (ACSI-28), achievement motivation (AMSSE and PSI) and activation control (PSI). The classification functions that were developed from these variables had an 86.11% success rate in classifying the soccer players into their original separate groups. The results of the study justify the inclusion of sport psychological skills in soccer talent identification protocols for young players.